Increasing Liana Abundance and Associated Reductions in Tree Growth in Secondary Seasonally Dry Tropical Forest - Becknell, Justin M.; Vargas G., German; Wright, Lacey A.; Woods, Natalie-Francesca; Medvigy, David; Powers, Jennifer S. (Frontiers in Forests and Global Change, 2022)
Lianas are thought to be increasing and altering tree growth and ecosystem productivity in tropical forests, but less research has focused on secondary or seasonally dry tropical forest. We report on an 11-year study of tree growth and liana presence from Guanacaste, Costa Rica, where we measured the diameter growth and liana presence on more than 1,700 trees in regenerating forest of different ages. We find that the proportion of trees without lianas is decreasing and the number of trees with lianas occupying more than 10% of tree’s crowns is increasing. We also find that lianas are affecting the diameter growth of trees. The 11-year average relative growth rates of trees with lianas in more than 10% of the tree’s crown are lower than the relative growth of trees with no lianas or lianas in less than 10% of their crown. Year-to-year, tree relative growth rate is related to annual precipitation and tree diameter. However, trees that were heavily infested with lianas (i.e., with lianas in more than 50% of their crowns) had lower relative growth and a weaker precipitation-growth relationship. This work underscores the value of long-term longitudinal data in secondary forest and adds critical data on dry forest liana abundance change.